A study of children’s participation in peacebuilding in a post- conflict society: a case study of peace clubs in Gulu, Uganda - Gulliksen, Cecilie (2015)
The general aim of the study was to get an understanding how children participate in peacebuilding and how it is supported in a post-conflict society like Gulu. Gathering information in Gulu, Northern Uganda approached this aim. The four components that together created the “understanding” were; the actions the children took towards creating peace in their own surroundings and the sort of effects these actions had, children and adults interacting in peacebuilding, challenges that children participating in peacebuilding faced; Partners working with children participating in peacebuilding and the kind of support they provided. The data collection was done through eight focus groups; in addition four key informant interviews were conducted with open-end questions. The focus group contained a mix of three different tools; body-map, timeline and Venn diagram. The tools have been adapted to peacebuilding by Save the Children for children to evaluate their own level of participation in peacebuilding. The results from the tools together with transcriptions from the focus groups and the key informant interview were analysed through a thematic analysis. The themes presented and interpreted were; peacebuilding activities, changes towards peaceful behaviour (past and present), adult perceptions of children’s participation, support from the church and the local community to the peace clubs, challenges and significance of participation. These themes all presented different captions of how peace clubs in Gulu interacted. The activities, actions and cognitive state of the children linked to peacebuilding formed various pictures of what peacebuilding is. Participation was a constant negotiation between adults and children. The children’s perception was influenced by war and cultural circumstance. Support to children’s work with peacebuilding is coherent with their activity agenda; which caused speculation about the level of children’s participation in peacebuilding in Gulu. Recommendations for further studies; to investigate more about the local networks around peacebuilding in areas similar to Gulu; measure and evaluate, to what extent, the effect of child participation has on the personal growth of a child and how that growth reaches and effects the community; to assess the similarities between child and adult, a study of the adults’ vision of participation should be introduced over a continuous period of time; investigate how the UNCRC article 12.1 limits but also enhances children’s participation. Finally, where recommendation to increase children’s participation in peacebuilding has been taken, a study of the Gulu community’s peacebulding work is required. This studies aim is to assist, guide and hopefully to ensure a continuing path to a peaceful society.